Somatic, Auditory, Visual, dan Intellectual (SAVI) : Solusi Cerdas untuk Mengoptimalkan Capaian Belajar Peserta didik pada Mata Pelajaran Pendidikan Pancasila - Umay, SITI; Rahman, MS Khabibur; Painem, Painem (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
In the context of education, learning outcomes are the main target as well as an indicator of the effectiveness of the learning process. Basically, learning outcomes reflect the accumulation of various learning activities carried out by students. This research shows that the Somatic, Auditory, Visual, and Intellectual (SAVI) learning model has a significant positive impact on improving students' learning outcomes. The SAVI learning model emphasises the active participation of learners in the learning process through the use of all five senses so that the learning process becomes more comprehensive and meaningful. The research method used was Classroom Action Research (PTK) with two cycles. The results of the analysis in cycle I obtained the average score of students which was 63.5 with the predicate ‘Very Less and Less’. After the application of the SAVI learning model, there was an increase in cycle II to 80 with the majority of students (70%) in the predicate ‘Very Good’ and the absence of the predicate ‘Very Poor’. This SAVI learning model can be implemented by teachers as an alternative in learning activities to encourage students to be more enthusiastic and active in learning during the learning process.